CONCERNING ONE OF THE LAST SHEIBANID SULTANS OF THE FERGHANA VALLEY (TAMADDUN NURI JURNALI, 2024)
This article discusses the political processes in the Bukhara Khanate at the end of the XVI-early XVII century, the influence of the transition of power from the Sheibanids to the Ashtarkhanids on the Fergana Valley. As a result of a series of raids by nomadic Kazakh-Kyrgyz tribes from the northeast during this period, the Bukhara Khanate lost part of its territories acquired under Abdullah Khan II. The fierce political struggle of that time did not pass by the Ferghana Valley either. In the struggle for Tashkent and the Syrdarya territories, the Ashtarkhanids fought against the Kazakh khans, and for the Ferghana Valley, political interests clashed with Keldimukhammadkhan.